Estudo da adsorção do corante vermelho astrazon utilizando bentonita - Bueno, Raquel de Freitas Greco (2015)
The adsorption of different contaminants, including, dyes, natural adsorbents have been increasingly studied for the purpose of improving the process for its application in the environment. The aim of this study was Astrazon red dye and the objective was to evaluate the adsorptive potential of bentonite clay aimed at removing the red dye Astrazon when applied fresh and after heat treatment. For evaluating the influence of treatment completion in the performance of bentonite as adsorbent were performed calcinations to 5000C for times ranging 2-32 hours. Seeking to verify morphological changes in the material due to the heat treatment, electron microscopy analyzes were performed scan with Energy Dispersive Spectrometer. From the results obtained it was possible to determine an 90% removal of the dye in the middle of the bentonite in nature, especially when compared to calcined clay, since they resulted in slower and less efficient adsorption compared to untreated. The adsorption capacity of red dye Astrazon the bentonite was estimated, considering its application in the environment, through a prior assessment kinetics to determine a possible kinetic model that best represents it, which in this case was the kinetic model of pseudo second order. From these analyzes, it is concluded that the bentonite in nature is an effective adsorbent for the removal process Astrazon Red dye from the aqueous medium.